TREATMENT OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES CONSIDERING THE ASSESSMENT OF THE DEGREE OF IMPAIRMENT OF NON-RESPIRATORY LUNG FUNCTION - Bobokulova , Sh.; Khamdamov , Sh.; Bobobekov , A.; Sattarov , I.; Boboev , Q.; Abdurakhmanov , F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The objective & methods: program of pre-operative preparation was developed based on examination and treatment of patients with acute purulent destructive pulmonary diseases (APDPD) with regard to process phase (Group 1 - septic process flow, Group 2 - stabilization, Group 3 - remission), endotoxemia severity, and non-respiratory function of lungs (NRFL). Group I patients under basic long-term intra-arterial catheter-based therapy (LIACT) followed our developed NRFL correction scheme and treated suppurative focuses with electrolyzed sodium hypochlorite solution. It has proven to be efficient for 202 (79,9%) out 254 Group 1 patients, enabling withdrawal from surgery, while only 52 (40.6%) of Group 2 patients and 26 (31.3%) of Group 3 patients have not undergone surgery. Results & conclusion: simultaneously, clear NRFL malfunction degree correction augmenting impact was achieved accompanied by limiting and stabilizing the process. It has enabled to limit lung resection numbers to 109 (60.9%) out of 179 Group 1 patients who undergone surgery with 8,7% of surgical complications comparing to 18.4% for Group 2 and 24,6% for Group 3, emphasizing the efficiency of the pre-operative preparation strategy we proposed. Key words: pre-operative preparation, acute purulent destructive pulmonary diseases, non-respiratory function of lungs, long-term intra-arterial catheter-based therapy